MARKETING STRATEGIES AND CONSUMER PURCHASE DECISIONS: THE ROLE OF PRODUCT QUALITY, CUSTOMER SATISFACTION, AND BRAND IMAGE IN VISUAL AND CULTURAL CONSUMPTION CONTEXTS - Arora, Rahat; Singh, Harvinder (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Consumers in modern markets are making choices on what they will buy based upon more than just functional characteristics, but being influenced by visual, artistic, and cultural factors. This conceptual paper seeks to come up with a holistic model of consumer purchase decisions in contexts of visual, performing and cultural consumption. Based on the existing marketing constructs, the paper assesses how product quality and customer satisfaction are antecedents that affect brand image, which subsequently leads to purchase decisions. Using the argument that the visual appeal, artistic expressions, and symbolic meanings would improve consumer perceptions and brand association, the paper maintains that culturally enriched and aesthetically motivated consumption environments would be more beneficial to consumer perceptions and brand associations. Combining conventional marketing variables with the findings of the visual and cultural consumption literature, the work offers a multidisciplinary approach which identifies the similarity of consumer behavior to the fields of performing and visual arts. The suggested conceptual framework has a contribution to both marketing and arts-based research because it brings out the topicality of aesthetic and cultural aspects in influencing consumer decision-making. The paper also provides a guideline to future empirical studies to prove the proposed relationships in different cultural contexts